Qualidade da informação: o caso da organização prestadora de serviços baseados em informação - Silva, Antonio Carlos Santos (Universidade Federal de São Carlos, 2013)
Information has become essential for organizational performance and more rational and sustainable decision-making about work processes and competitive in the organizational context. Based on the quality model presented by Albrecht (1999), this work has the general objective of developing and applying a system for the diagnosis and evaluation of the quality of information in the organizational context. To achieve this objective, the exploratory case study research method was used and the case unit was an organization providing information-based services, located in the city of São Carlos-SP. The results obtained were: 1] proposal of a systematic for the diagnosis and evaluation of the quality of the information in the organizational context; 2] Mapping the information flow of the case unit; 3] Identification of key jobs and their information needs; 4] Collection and analysis of the workers' perceptions of the case unit about information quality. It is concluded based on the results achieved, that the knowledge generated in this work can contribute to the efficiency and effectiveness of the performance of organizations that provide information-based services by providing a system that enables the diagnosis and assessment of the quality of information in the organizational context.
Quality of information: the case of the organization providing information-based services
Keywords: Fluxo de informação; Qualidade da informação; Qualidade total; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO